Answer:
Option A is correct.
Explanation:
We need to find the product of
![((x^2-16))/((2x+8)) * ((x^3-2x^2+x))/((x^2+3x-4))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8ds67tn95w9r8ao6xts1iltzyggj4j3hg0.png)
We know (a^2-b^2) = (a+b)(a-b)
so, (x^2-16) = (x)^2-(4)^2 = (x-4)(x+4)
2x+8 Taking 2 common from this term:
2x+8 = 2(x+4)
(x^3-2x^2+x) Taking x common from this term
x(x^2-2x+1) = x(x-1)^2 = x(x-1)(x-1)
(x^2+3x-4) factorizing this term
x^2+4x-x-4 = x(x+4)-1(x+4)
= (x-1)(x+4)
Now, Putting these simplified terms in the given equation:
![((x-4)(x+4))/(2(x+4))*(x(x-1)(x-1))/((x-1)(x+4))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/f4cr1azujlzyclimqsa70n3np42pc1xvku.png)
Now cancelling the same terms that are in numerator and denominator
![=((x-4))/(2)*(x(x-1))/((x+4))\\=((x-4)(x)(x-1))/(2(x+4))\\=(x(x-4)(x-1))/(2(x+4))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/y4xjajdqwn3kqz5o5z6dvuevs8yu3ddfe5.png)
So, Option A is correct.